Analisis Manajemen TIK Terhadap Keamanan Informasi Dan Manajemen Risiko Perpustakaan - Paramita, Silvia (Universitas Bojonegoro, 2023)
This research examines the role of IT management in improving information security and library risk management. It underscores the importance of references in validating information, particularly within education, where libraries are key in providing resources. With the growth of online libraries, technological advancements bring new risks, including threats to data confidentiality, integrity, and availability, requiring updated risk management strategies. The study highlights the need for information systems integrated with reliable technology to address these risks and enhance library operations. It also explores various risk types and methods for assessing and managing them, focusing on how IT can bolster security and reduce risks associated with outdated systems. The research concludes that effective risk management, including continuous assessment and technology updates, is critical to protecting library assets.